DEVELOPMENT OF PROJECT-BASED LEARNING DIGITAL WORKSHEETS TO ENHANCE INDONESIAN LANGUAGE LEARNING OUTCOMES IN FIFTH-GRADE ELEMENTARY STUDENTS - Ni Luh Putu Rani Diana Putri; Gusti Ayu Sri Wijastini; Ni Luh Putu Ani Lestiani; Ni Nyoman Kurnia Wati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aimed to develop and evaluate a Project-Based Learning (PjBL)-based digital Student Worksheet (LKPD) to improve Indonesian language learning outcomes for fifth-grade students in Cluster 4 of Tabanan District. Using a Research and Development approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study employed a quasi-experimental pretest–posttest control group design involving 56 fifth-grade students divided into experimental (PjBL-based digital LKPD) and control (conventional printed LKPD) groups. Data were collected through expert validation sheets, teacher and student practicality questionnaires, and learning achievement tests. Validity testing yielded an overall mean score of 3.48 (>3.00), categorized as